Central Chadic numerals in comparative perspective - Blažek, Václav (Lingua Posnaniensis, 2024)
The present study summarizes the forms of numerals of the first decade in more than 200 Central Chadic languages and their varieties, including their sources, to analyze their internal structure and external relations, in both genetic and areal plans.